2007
DOI: 10.1111/j.1365-313x.2006.03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the sucrose synthase gene family in Arabidopsis

Abstract: ). † These authors contributed equally to the work. SummaryThe properties and expression patterns of the six isoforms of sucrose synthase in Arabidopsis are described, and their functions are explored through analysis of T-DNA insertion mutants. The isoforms have generally similar kinetic properties. Although there is variation in sensitivity to substrate inhibition by fructose this is unlikely to be of major physiological significance. No two isoforms have the same spatial and temporal expression patterns. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
317
3
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(352 citation statements)
references
References 61 publications
18
317
3
4
Order By: Relevance
“…In contrast, its homolog AtSUS1 increases under stress (Ma et al, 2006). AtSUS1 also responds to elevated carbohydrate concentrations (Bieniawska et al, 2007). However, our metabolite profiling did not provide evidence for strong redirecting of carbohydrate metabolism during salt stress.…”
Section: Discussion Different Transcriptional Timetables Of Salt Respcontrasting
confidence: 43%
“…In contrast, its homolog AtSUS1 increases under stress (Ma et al, 2006). AtSUS1 also responds to elevated carbohydrate concentrations (Bieniawska et al, 2007). However, our metabolite profiling did not provide evidence for strong redirecting of carbohydrate metabolism during salt stress.…”
Section: Discussion Different Transcriptional Timetables Of Salt Respcontrasting
confidence: 43%
“…However, it seems highly unlikely that SUS5 and SUS6 are outside the cell. Both have kinetic properties, including a neutral pH optimum, similar to other, intracellular SUS isoforms (Bieniawska et al, 2007). We suggest that GSL7, SUS5, and SUS6 may form part of a tight complex that spans the plasma membrane of the sieve element and links into the wall.…”
Section: Callose Synthesis In the Phloem May Differ From That In Othementioning
confidence: 99%
“…Studies of the predicted amino acid sequences and gene structure have shown that the Arabidopsis SUS family consists of six SUS genes displaying different developmental expression patterns (40,41). The involvement of SUS in starch and cellulose biosynthesis in Arabidopsis has been recently questioned by Bieniawska et al (42) and Barratt et al (43), who showed that (i) leaves, siliques, stems, and roots of the sus1/sus2/sus3/sus4 quadruple SUS mutant impaired in SUS activity accumulate WT content of ADPG, UDPG, cellulose and starch, and (ii) SUS activity in WT leaves is too low to account for the rate of starch accumulation in illuminated leaves. However, these authors assayed SUS activity in the sucrose synthetic direction under conditions that are far from optimal, which inadvertently lead to their conclusion.…”
mentioning
confidence: 99%
“…Several assay conditions that departed from optimal were: First, the SUS reaction assay mixture used by the authors contained 6 mM fructose, a concentration comparable to or lower than the reported K m values for fructose in SUS from many species (10,11,44). Second, the pH of the SUS reaction assay mixture used by Bieniawska et al (42) and Barratt et al (43) was 9.4, which is far too basic with respect to both cytosolic pH and to previously reported optimum pH values for SUS activity in the synthetic direction (10,(45)(46)(47)(48). Third, SUS assay reactions were stopped after 20 min of incubation, a condition that does not allow the attainment of reliable data under SUS initial velocity conditions.…”
mentioning
confidence: 99%